Progress Towards a New World Economic Order - Gardner, Richard N.; Vambery, Robert G. (Journal of International Business Studies, 1975)
The authors contrast the approaches advocated by major power blocks for lessening the gap between the economic levels of industrialized and developing countries. The LDC's are seeking resource transfers favorable to them. The industrialized nations are willing to help but in ways that avoid undue harm to their internal economies and to the security of their direct investments. Hopefully, negotiations rather than confrontations will be used to resolve the conflict.